Exploring Sharia-Compliant Fintech Equity Crowdfunding: New Opportunities for Business Financing - Haanurat, A. Ifayani (CV. Bimbingan Belajar Assyfa, 2025)
In recent years, the rise of fintech has revolutionized the landscape of business financing, offering innovative solutions that align with ethical frameworks. This study delves into the potential of Sharia-compliant fintech equity crowdfunding as a transformative tool for business financing, particularly for entrepreneurs and small to medium-sized enterprises (SMEs) seeking alternative funding routes. Unlike traditional financial systems, Sharia-compliant crowdfunding adheres to Islamic principles, focusing on equity-based financing which prohibits interest (riba) and promotes risk-sharing. This research aims to bridge the gap in existing literature by exploring new theories and concepts surrounding this financing method, examining its practical application and potential benefits. The study adopts a mixed-methods approach, combining qualitative and quantitative data collection techniques. Surveys and in-depth interviews were conducted with 200 business actors across diverse sectors and regions, focusing on their experiences and perceptions of Sharia-compliant equity crowdfunding. Additionally, case studies of successful crowdfunding campaigns were analyzed to highlight effective strategies and common challenges faced by participants. Data analysis was performed using thematic analysis for qualitative data and statistical methods for quantitative data, providing a comprehensive picture of the current landscape. The findings reveal that Sharia-compliant equity crowdfunding significantly enhances financial inclusion by offering a viable financing avenue that aligns with ethical values, thereby attracting a broader range of investors. Moreover, businesses that have embraced this financing method reported substantial growth and development, indicating a positive correlation between Sharia-compliant crowdfunding and economic advancement. However, the study also identifies several barriers to widespread adoption, including limited awareness and understanding of Sharia financing principles, as well as restricted access to platforms in certain regions. To address these challenges, the research suggests implementing targeted educational initiatives and improving platform accessibility to maximize the potential benefits of Sharia-compliant equity crowdfunding.